End-of-Life Vehicles (ELVs) in Malaysia: Time for Action to Guarantee Vehicle Safety - Abu Kassim, K.A.; Abu Husain, N.; Ahmad, Y.; Mohd Jawi, Z. (Journal of the Society of Automotive Engineers Malaysia, 2020)
It is envisaged that by the end of 2020, the number of passenger cars ever registered will reach 9.97 million with further projection to 12.64 million by 2040. While most new cars sold in Malaysia have reached ASEAN NCAP's 4- or 5-star rating by improving their safety standards, we can still see aged cars on the road. If the ELV policy were to be enacted in Malaysia, not only the country's economy will flourish but also ASEAN NCAP's endeavours would surely be more fruitful. Nonetheless, the question remains; will there be any policies or regulations regarding old cars in Malaysia such as those implemented in developed countries? In the end, the public must be convinced that an old car with inferior safety features on the road can ultimately lead to a tragedy and should fundamentally outweigh the economic implications to the consumers.